Extension, advice and knowledge systems for private forestry: Understanding diversity and change across Europe. (May 2020) - Lawrence, Anna; Deuffic, Philippe; Hujala, Teppo; Nichiforel, Liviu; Feliciano, Diana; Jodlowski, Krzysztof; Lind, Torgny; Marchal, Didier; Talkkari, Ari; Teder, Meelis; Vilkriste, Lelde; Wilhelmsson, Erik
Highlights: FOrestry Knowledge and Information Systems (FOKIS) in Europe are changing as ownership and policy change. Patterns of persuasive or coercive communication vary with geography and politics. Policy demands from forests are broadening from timber to wider ecosystem services. FOKIS are becoming more democratic, participatory and negotiated. Advisory services are moving from public to private sector. Abstract: The decisions and actions of private forest owners are important for the delivery of forest goods and services. Both forest ownership, and policies related to forest owners, are changing. Traditionally in most countries, government extension officers have advised and instructed forest owners, but this is evolving, with greater importance given to a range of actors, objectives, and knowledge types. Drawing on literature and mixed data from 10 countries in Europe, this paper explores how forestry advisory systems can be conceptualized, and describes their current situation in Europe. Drawing parallels with the concept of AKIS (Agricultural Knowledge and Information Systems), we propose the term FOKIS (FOrestry Knowledge and Information Systems), as both a system (a purposeful and interdependent group of bodies) and a method for understanding such systems. We define four dimensions for describing FOKIS: owners, policy goals, advice providers, and tools. We find different roles for extension in countries with centrally controlled, highly regulated forest management, and advisors in regions where forest owners have more freedom to choose how to manage their forest. We find five trends across Europe: increasing flexibility, openness and participation of owners as sources of information; increasing reliance on information and persuasion rather than enforced compliance; a shift of attention from timber to a wider range of ecosystem services such as biodiversity and recreation; a shift of funding and providers from public to private sector; emergence of new virtual communication tools. The approach provides a way to make sense of comparisons and change in FOKIS, and opens up an important research field.